Spotting intruders: Species distribution models for managing invasive intertidal macroalgae. (1st March 2021) - Blanco, A.; Larrinaga, A.R.; Neto, J.M.; Troncoso, J.; Méndez, G.; Domínguez-Lapido, P.; Ovejero, A.; Pereira, L.; Mouga, T.M.; Gaspar, R.; Martínez, B.; Lemos, M.F.L.; et al.
Abstract: Invasive macroalgae represent one of the major threats to marine biodiversity, ecosystem functioning and structure, as well as being important drivers of ecosystem services depletion. Many such species have become well established along the west coast of the Iberian Peninsula. However, the lack of information about the distribution of the invaders and the factors determining their occurrence make bioinvasions a difficult issue to manage. Such information is key to enabling the design and implementation of effective management plans. The present study aimed to map the current probability of presence of six invasive macroalgae: Grateloupia turuturu, Asparagopsis armata, Colpomenia peregrina, Sargassum muticum, Undaria pinnatifida, and Codium fragile ssp. fragile . For this purpose, an extensive field survey was carried out along the coast of the north-western Iberian Peninsula. Species distribution models (SDMs) were then used to map the presence probability of these invasive species throughout the study region on the basis of environmental and anthropogenic predictor variables. The southern Galician rias were identified as the main hotspots of macroalgal invasion, with a high probability of occurrence for most of the species considered. Conversely, the probability of presence on the Portuguese coast was generally low. Physico-chemical variables were the most important factors for predicting the distribution of invasive macroalgae contributing between 57.27 and 85.24% to the ensemble models. However, anthropogenic factors (including size of vessels, number of shipping lines, distance from ports, population density, etc.) considerably improved the estimates of the probability of occurrence for most of the target species. This study is one of the few to include anthropogenic factors in SDMs for invasive macroalgae. The findings suggest that management actions aimed at controlling these species should strengthen control and surveillance at ports, particularly in southern Galician rias. Early detection should be of main concern for risk assessment plans on the Portuguese coast. Graphical abstract: Image 1 Highlights: Correlative SDMs provide much-needed information for managing invasive macroalgae. Anthropogenic factors influence the distribution of all macroalgae, except C. fragile . The southern Galician rias and Ria da Coruña are hotspots for invasive macroalgae. Codium fragile should be monitored in Portugal for early detection. Management of invasive macroalgae should focus on ports and densely populated areas.